Multimodal representational gestures in the transition to multi‐word productions. (23rd November 2020) - Murillo, Eva; Casla, Marta
Abstract: The aim of this study was to analyze the use of representational gestures from a multimodal point of view in the transition from one‐word to multi‐word constructions. Twenty‐one Spanish‐speaking children were observed longitudinally at 18, 21, 24, and 30 months of age. We analyzed the production of deictic, symbolic, and conventional gestures and their coordination with different verbal elements. Moreover, we explored the relationship between gestural multimodal and unimodal productions and independent measures of language development. Results showed that gesture production remains stable in the period studied. Whereas deictic gestures are frequent and mostly multimodal from the beginning, conventional gestures are rare and mainly unimodal. Symbolic gestures are initially unimodal, but between 24 and 30 months of age, this pattern reverses, with more multimodal symbolic gestures than unimodal. In addition, the frequency of multimodal representational gestures at specific ages seems to be positively related to independent measures of vocabulary and morphosyntax development. By contrast, the production of unimodal representational gestures appears negatively related to these measures. Our results suggest that multimodal representational gestures could have a facilitating role in the process of learning to combine meanings for communicative goals.